(untitled) (The Conference Hub, 2025)
This thesis explores the significant role of grammar in shaping meaning, style, and interpretation in both Uzbek and English literary texts. While grammar is often perceived merely as a set of structural rules, in literary contexts it functions as a powerful tool for authors: helping to foreground thematic elements, control narrative voice, and reflect cultural-linguistic particularities. Through comparative analysis, we examine syntactic, morphological, and pragmatic dimensions of grammar, showing how grammatical choices in both languages contribute to aesthetic effect, coherence and cultural expression.